(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Neonatal septicemia is one of the major health problems throughout the world. Infections are a frequent and important cause of morbidity and mortality in neonatal period. Objective: The objective of this study was the role of hematologic scoring system (HSS) in the early diagnosis of neonatal septicemia. Methods: This is a prospective study consisted of 100 neonates admitted at neonatal ICU, BSMMU, who were clinically suspected cases of septicemia. The neonatal hematological parameter was measured in all cases. Blood culture was done for the gold standard of proven sepsis. There were 12 out of 100 neonates (12%) who had culture proven sepsis. They were predominantly preterm and of very low birth weight. Results: On evaluation of various hematological parameters total leucocytes count, total neutrophil count, IT ratio (>0.2), IM ratio (> 0.3), total immature PMNs count, platelet count were found to have optimal sensitivities and negative predictive values. Using these values hematologic scoring system was formulated according to Rodwell et al. Score > 4 has a sensitivity of 100%, specificity of 60%, with PPV 26% and NPV 100 %. Considering the high sensitivity, negative predictive value, this study implies that score > 4 were more reliable as a screening tool for sepsis than any of the individual hematological parameter. Conclusion: HSS are useful test to distinguish the infected from non infected infants. They also provide a effective guideline to make decisions regarding judicious use of antibiotic therapy. Keywords: Hematologic scoring system (HSS); Blood culture; Neonatal septicemia DOI: 10.3329/bsmmuj.v3i2.7053 BSMMU J 2010; 3(2): 62-67